Kiai-AI: Renegotiating Religious Authority in the Digital Age - Tarwiyyah, Hanik Lailatut (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This research examines the impact of Artificial Intelligence (AI) on religious authority, specifically the role of Kiai and Ulama in Indonesia. AI offers opportunities to enhance the accessibility and efficiency of religious practices but poses challenges related to authenticity and religious hierarchy. The research method used is a literature review and document analysis, involving the collection and review of various sources such as journal articles, research reports, and online news. The findings indicate that AI has been adopted in various religious practices, including virtual preachers, prayer bots, and personalized religious guidance tools. However, there are significant concerns regarding AI's authenticity and authority in providing religious guidance, reflected in the prohibition of AI fatwas by major Islamic organizations in Indonesia. The